Globalization Reappraised : a Talisman or a False Oracle. - Vajpeyi, Dhirendra K. (Globalization and its costs., 2017)
This book analyzes and examines the political and economic factors that contributed to the emergence of globalization approaches in the post-Cold War era, and the reappraisal of globalization since the global financial crisis.